Human Tudor staphylococcal nuclease (Tudor‐SN) protein modulates the kinetics of AGTR1‐3′UTR granule formation. Issue 13 (8th May 2014) - Gao, Xingjie; Shi, Xuebin; Fu, Xue; Ge, Lin; Zhang, Yi; Su, Chao; Yang, Xi; Silvennoinen, Olli; Yao, Zhi; He, Jinyan; Wei, Minxin; Yang, Jie
Abstract : Human Tudor staphylococcal nuclease (Tudor‐SN) interacts with the G3BP protein and is recruited into stress granules (SGs), the main type of discrete RNA‐containing cytoplasmic foci structure that is formed under stress conditions. Here, we further demonstrate that Tudor‐SN binds and co‐localizes with AGTR1‐3′UTR ( 3′‐untranslated region of angiotensin II receptor, type 1 mRNA) into SG. Tudor‐SN plays an important role in the assembly of AGTR1‐3′UTR granules. Moreover, endogenous Tudor‐SN knockdown can decrease the recovery kinetics of AGTR1‐3′UTR granules. Collectively, our data indicate that Tudor‐SN modulates the kinetics of AGTR1‐3′UTR granule formation, which provides an additional biological role of Tudor‐SN in RNA metabolism during stress. Abstract : Tudor‐SN binds and co‐localizes with AGTR1‐3′UTR ( 3′‐untranslated region of angiotensin II receptor, type 1 mRNA) in SG. Tudor‐SN plays an important role in the assembly of AGTR1‐3′UTR granules. Tudor‐SN knockdown decreases the recovery kinetics of AGTR1‐3′UTR granules. Our results suggest an additional biological role of Tudor‐SN in RNA metabolism during stress.